Komparatif Pelaksanaan Pidana Mati Antara Hukum Acara Pidana Indonesia Dan Hukum Acara Pidana Thailand - Riri Alip Wibowo; Frendi Rushadinata; Robbi Kurnia Pratama; Jidan Ramadhan Jordan (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
The death penalty represents the most severe form of punishment in criminal law and is still retained by several countries, including Indonesia and Thailand. Although both countries are retentionist, they demonstrate significant differences in regulating and implementing capital punishment through their criminal procedure laws. This study aims to comparatively analyze the regulation and implementation of the death penalty in Indonesian and Thai criminal procedure law, as well as to assess the extent to which procedural mechanisms ensure the protection of death row inmates’ rights. This research employs a normative legal method using statutory, conceptual, and comparative approaches. The findings reveal that Indonesian criminal procedure law emphasizes legal certainty and the finality of court decisions, whereas Thailand prioritizes procedural flexibility through effective clemency mechanisms and a de facto moratorium. These differences indicate that the legitimacy of the death penalty is largely determined by the quality of due process of law rather than merely by the existence of substantive criminal norms. This study is expected to contribute to the development of comparative criminal law and to inform future reforms of criminal procedure law in Indonesia